Biodegradable Inorganic Nanovector: Passive versus Active Tumor Targeting in siRNA Transportation. Issue 14 (16th February 2016) - Park, Dae‐Hwan; Cho, Jaeyong; Kwon, Oh‐Joon; Yun, Chae‐Ok; Choy, Jin‐Ho
Abstract: The biodegradable inorganic nanovector based on a layered double hydroxide (LDH) holds great promise for gene and drug delivery systems. However, in vivo targeted delivery of genes through LDH still remains a key challenge in the development of RNA interference therapeutics. Here, we describe in vivo and in vitro delivery system for Survivin siRNA (siSurvivin) assembled with passive LDH with a particle size of 100 nm or active LDH conjugated with a cancer overexpressing receptor targeting ligand, folic acid (LDHFA), conferring them an ability to target the tumor by either EPR‐based clathrin‐mediated or folate receptor‐mediated endocytosis. When not only transfected into KB cells but also injected into xenograft mice, LDHFA/siSurvivin induced potent gene silencing at mRNA and protein levels in vitro, and consequently achieved a 3.0‐fold higher suppression of tumor volume than LDH/siSurvivin in vivo. This anti‐tumor effect was attributed to a selectively 1.2‐fold higher accumulation of siSurvivin in tumor tissue compared with other organs. Targeting to the tumor with inorganic nanovector can guide and accelerate an evolution of next‐generation theranosis system. Abstract : Cancer therapy : An inorganic layered double hydroxide (LDH) nanovector with a folic acid (FA) conjugated surface showed siRNA‐based cancer therapeutic efficacy in vivo through receptor‐mediated active targeting (see picture). A 1.2‐fold higher accumulation of the drug was achieved in tumor tissue, resulting in 3.0‐fold higher suppression of tumor volume.